Integrasi Nilai-Nilai Pendidikan Islam dalam Konteks Pendidikan Nasional - Hikma Nurfadila; Opik Taufik Kurrahman; Dadan Rusmana (Journal of Creative Student Research, 2024)
The integration of Islamic education values within the context of national education is a strategic step to shape a generation with strong character and global competitiveness. Islamic education, grounded in the principles of faith, ethics, and knowledge, aligns with the goals of national education, which emphasize the development of individuals who are devout, morally upright, and virtuous. This article employs a literature review to analyze the role of Islamic education in national education, exploring implementation opportunities, challenges, and strategies to achieve effective integration. The findings reveal that Islamic education values can be implemented through character education, school culture, and learning activities that emphasize moral and spiritual development. However, challenges such as inadequate teacher competencies, limited teaching materials, and resistance to religion-based approaches remain significant barriers. Recommended strategies include teacher training, the development of relevant teaching materials, and collaboration with stakeholders to create an inclusive educational ecosystem. With these approaches, Islamic education not only becomes a part of national education but also acts as a catalyst for fostering a generation that excels both academically and ethically. The article concludes that Islamic education is a vital asset in achieving the goals of national education amidst the challenges of globalization.